Defining hunger, redefining food: humanitarianism in the twentieth century - Scott-Smith, T (2014)
This thesis concerns the history of humanitarian nutrition and its political implications. Drawing on aid agency archives and other historical sources, it examines how food has been delivered in emergencies, from the First World War to the present day. The approach is ethnographic: this is a study of the micro-level practices of relief, examining the objects distributed, the plans made, the techniques used. It is also historical: examining how such practices have changed over time. This thesis makes five interlocking arguments. First, I make a political point: that humanitarian action is always political, and that it is impossible to adhere to ‘classical’ humanitarian principles such as neutrality, impartiality and independence. Second, I make a sociological argument: that the activities of humanitarian nutrition have been shaped by a number of themes, which include militarism, medicine, modernity, and markets. Third, I make a historical argument: that the main features of humanitarian nutrition were solidified between the 1930s and the 1970s, and were largely in place by the time of the Biafran war. Fourth, I make a sociological argument: that these mid-century changes involved a profound redefinition of hunger and food (with hunger conceived as a biochemical deficiency, and food as a collection of nutrients). Finally, I make a normative argument, suggesting that this redefinition has not necessarily benefited the starving: the provision of food in emergencies, I argue, is often concerned with control and efficiency rather than the suffering individuals themselves.